2020
DOI: 10.1002/jsfa.10877
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of quercetin and sodium chloride concentrations on wheat gliadin structure and physicochemical properties

Abstract: BACKGROUND Polyphenols may interact with protein via covalent bonds and non‐covalent interactions, improving the structures and functional properties of the protein. The cross‐linking between the polyphenol and protein is susceptible to salt (sodium chloride, NaCl) concentrations. Our study investigated the combined effects of quercetin (Q) and NaCl concentrations on wheat gliadin (G) structure and physicochemical properties. RESULTS Q and NaCl addition resulted in a more compact protein microstructure. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Disulfide bridges could be classified into three different spectral ranges (500–515, 515–525, and 525–545 cm –1 ), which represented the orientational sequence of g–g–g, g–g–t, and t–g–t, respectively. The conformation of g–g–g was regarded as the most energetically stable and associated with interchain disulfide bonds, whereas g–g–t was related to the intrachain disulfide bonds in wheat gluten . Multipeak Gaussian fitting was used to analyze the deconvolution of the disulfide bridges spectral region to obtain the band profiles of the Gaussian components for each sample .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disulfide bridges could be classified into three different spectral ranges (500–515, 515–525, and 525–545 cm –1 ), which represented the orientational sequence of g–g–g, g–g–t, and t–g–t, respectively. The conformation of g–g–g was regarded as the most energetically stable and associated with interchain disulfide bonds, whereas g–g–t was related to the intrachain disulfide bonds in wheat gluten . Multipeak Gaussian fitting was used to analyze the deconvolution of the disulfide bridges spectral region to obtain the band profiles of the Gaussian components for each sample .…”
Section: Resultsmentioning
confidence: 99%
“…The conformation of g−g−g was regarded as the most energetically stable and associated with interchain disulfide bonds, whereas g−g−t was related to the intrachain disulfide bonds in wheat gluten. 43 Multipeak Gaussian fitting was used to analyze the deconvolution of the disulfide bridges spectral region to obtain the band profiles of the Gaussian components for each sample. 43 As shown in Figure 4D-4, the percentages of disulfide bridges in the native wheat gluten (CK) were 88% g− g−g and 12% t−g−t, which suggested that the tertiary structure of native wheat gluten was stable.…”
Section: Journal Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Wang et al investigated the combined effects of quercetin and NaCl concentration on the wheat gliadin structure and physicochemical properties, and emphasized the benefit of natural food additives in food processing. 16 Until now, to the best of our knowledge, there are seldom studies systemically concentrated on elucidating the interaction between dietary flavonoids and gliadin. Therefore, in the present study, the relationship of the molecular structure and the binding affinity between a series of flavonoids (structure seen in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…15 Wang et al investigated the combined effects of quercetin and NaCl concentration on the wheat gliadin structure and physicochemical properties, and emphasized the benefit of natural food additives in food processing. 16…”
Section: Introductionmentioning
confidence: 99%